Classification of chronic pain for the International Classification of Diseases (ICD-11): results of the 2017 international World Health Organization field testing - Barke, Antonia; Korwisi, Beatrice; Jakob, Robert; Konstanjsek, Nenad; Rief, Winfried; Treede, Rolf-Detlef (Pain, 2022)
Because chronic pain has been poorly represented in the International Statistical Classification of Diseases and Related Health Problems (ICD) despite its significant contribution to the burden of disease worldwide, the International Association for the Study of Pain (IASP) developed a classification of chronic pain that was included in the ICD-11 version as “MG30” and approved by the World Health Assembly in 2019. The objective of this field test was to determine how well the classification of chronic pain works in the context of the ICD-11. A web-based survey using the WHO-FiT platform recruited 177 healthcare professionals from all WHO regions. After a training on coding chronic pain hosted by the IASP Web site, participants evaluated 18 diagnostic codes (lines) of the 2017 frozen version of the ICD-11 and 12 vignettes (cases) describing chronic pain conditions. Correctness, ambiguity, and perceived difficulty of the coding were compared between the ICD-11 and the ICD-10 and the applicability of the morbidity rules for the ICD-11 verified. In the line coding, 43.0% of correct chronic pain diagnoses assigned with the ICD-10 contrasted with 63.2% with the ICD-11. Especially in cases in which the chronic pain is regarded as the symptom of an underlying disease, the ICD-11 (63.5%) commanded more correct diagnoses than the ICD-10 (26.8%). The case coding was on average 83.9% accurate, only in 1.6% of cases any difficulty was perceived. The morbidity rules were applied correctly in 74.1% of cases. From a coding perspective, the ICD-11 is superior to the ICD-10 in every respect, offering better accuracy, difficulty, and ambiguity in coding chronic pain conditions.
Gesehen am 27.07.2023